Korean Crisis and a War of Words - Beczkowska, Joanna (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
In 2017, Korean crisis escalated as Donald Trump began “war of words” with DPRK’s chairman Kim Jong-un. Each threat both leaders made might eventually be understood by the other party as a declaration of war. Donald Trump wanted to “clean up the mess” left by previous US administrations and solve the problem of North Korean nuclear program. However, his actions were inconsistent: he threatened in a very North Korean way “total destruction” only to emphasize later that it was not a “preferred option.” This article explores how “war of words” was a significant cause of the escalation of the Korean crisis.